1968 en bande dessinée : histoire, technologie, pratiques culturelles - Vincze, Ferenc (Acta Romanica Quinqueecclesiensis : La publication du Département d’Études Françaises et Francophones, Université de Pécs, 2025)
The study focuses on the analysis of a Romanian graphic novel (Mickey pe Dunăre by Cristian Dârstar and Alexandru Berceanu). Through the personal stories of Czech families on holiday in Romania in 1968, this work presents the historical events that were decisive in August of that year. The story, told from a personal perspective, is set against the backdrop of the history of Eastern Europe, and the presentation of the cultural practices of the time gives the reader a comprehensive picture of everyday life in the period, in particular the technical means of information flow and the practices associated with it. In this way, the graphic novel creates a history of the region and provides an insight into the often forgotten world of the technical media of the time. The study also highlights the interconnections between history and media history and the importance of their parallel representation.